Facing Geographical Challenges and Human Resource Innovation at PT. PLN (Persero) UP3 Jayapura: A Turn Around Strategy Approach - Wulandari, Fadila; Srem, Ade Irma A.; Wanma, Johanis R. (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2025)
This study aims to analyze human resource development (HRD) strategies to improve employee performance at PT. PLN (Persero) UP3 Jayapura. A SWOT analysis approach was used to identify internal and external factors influencing the company’s HR management. The results indicate that PT. PLN (Persero) UP3 Jayapura is positioned in Quadrant II (WO) of the SWOT Matrix, which suggests the need for a Turn Around strategy that leverages external opportunities to address internal weaknesses. The proposed strategies include digitalizing HR management, developing technology-based training programs, optimizing internal communication, and improving performance-based compensation policies. The findings are expected to contribute to formulating more effective HR management policies in the energy sector, particularly in PLN units facing geographical challenges and limited infrastructure.